Kinetic and Isotherm Studies on Ciprofloxacin an Adsorption using Magnesium Oxide Nanopartices - Nahid Khoshnamvand, Shahin Ahmadi, Ferdos Kord Mostafapour (Journal of Applied Pharmaceutical Science, 2017)
The antibiotics along with the sewage, pharmaceutical industries water waste, veterinary clinics and hospital sewages and the agricultural products noticeably enter into the water resources and the environment. The objective of this study was to investigate ciprofloxacin removal efficiency from aqueous solutions by using Magnesium Oxide nanoparticles (MgO). The effects of pH, nanoparticles dose, contact time, initial antibiotic concentration were assessed on ciprofloxacin removal efficiency in laboratory. Under optimal conditions of concentration, the removal efficiency was 85%.and qm of the MgO nanoparticles was 3.46 mg/g. The process of ciprofloxacin adsorption on MgO nanoparticles was depended on Langmuir adsorption isotherm more than other isotherms. Batch kinetic experiments showed that the adsorption followed Pseudo second -order kinetic model with correlation coefficients greater than 0.978.
Keywords: Magnesium Oxide nanoparticle, Adsorption, Ciprofloxacin, Isotherm, kinetic.